Identities, Youth and Belonging International Perspectives - Habib, Sadia; Ward, Michael R. M. (Studies in Childhood and Youth, 2019)
This book contains empirical research from established and emerging scholars who draw upon interdisciplinary perspectives of space and place in order to investigate young people's sense of identities and belongings in diverse international contexts. The contributors aim to enhance our understanding of how theories of belonging are employed in the study of youth identity as these young people come to belong at a local, national, global, and even virtual level. The collection draws on research in the rural, the urban, and online, showcasing key sites and communities that play a role in young people's lives as they negotiate their sense of agency and sense of identity within the contexts of the locale. Identities, Youth and Belonging will be of interest to students and scholars across a range of disciplines including sociology, education, social policy, politics and geography. .